Impactos no perfil de tensão em redes de distribuição oriundos da inserção de geradores fotovoltaicos - AMARAL, Jhonny Pinto (2018)
Interest in renewable energy has grown considerably in recent years, due largely by concern for the environment and seek an alternative to fossil fuels, coupled to the need to expand the availability of energy to meet demand. This paper first presents a general approach and examples of renewable and alternative energy sources, with emphasis on solar energy. A brief history of photovoltaics is presented as well as the photovoltaic effect occurs for power generation, still showing the various types of cells available on the market. Solarimetric also presents maps of Brazil, showing radiation levels around the country, where generation is directly related to this factor. Showing measuring instruments that measure the incidence of solar radiation per unit area. Current legislation and incentives that exist in the country for distributed generation are presented, and the basic configuration of a system of residential photovoltaic generation. Finally, the IEEE 33 buses test system is used to simulate generators connected to power grid, given that this is a system widely used in distribution networks. Are evaluated voltage profiles, active and reactive losses in the system in various load scenarios and photovoltaic generation.